Blueberry Advisory System: A Disease Alert System for Blueberry Anthracnose Fruit Rot - André B. Gama; Douglas A. Phillips; Vinícius A. Cerbaro; Philip F. Harmon; Clyde W. Fraisse; Natalia A. Peres (EDIS)
The weather conditions favoring Blueberry anthracnose fruit rot disease incidence and development can be difficult to predict, and it can significantly impact yield under conducive weather patterns. For that reason, the authors of this new 6-page publication of the UF/IFAS Plant Pathology Department developed and validated a web-based disease alert system for blueberry AFR, the Blueberry Advisory System (BAS), to help blueberry growers in Florida identify weather conditions favorable for the disease and improve disease management. Written by André B. Gama, Douglas A. Phillips, Vinícius A. Cerbaro, Phillip F. Harmon, Clyde W. Fraisse, and Natalia A. Peres. https://edis.ifas.ufl.edu/pp366